Computer simulation as a basis for pharmacy reengineering. - Buchanan EC (Nursing Administration Quarterly)
Using computer simulation can enhance the management decision-making process. Simulations can predict the effects on cost and quality of services. This article discusses the use of computer simulation to assist in planning the reengineering process to change a hospital's drug distribution from a decentralized pharmacy satellite system to a centralized robotic drug dispensing system. Because computer simulation was based on a fixed set of circumstances, circumstances changed before system implemented. Nursing and pharmacy staff and line managers were involved in the review, planning, and implementation that resulted in positive economic and quality outcomes for this project. For organizations to achieve successful change, administrators must play an active and essential part.